Effect of Ginger on Chemical Composition, Physical and Sensory Characteristics of Chicken Soup - Duan, Wen (Foods, 2021)
In order to investigate the effect of ginger on taste components and sensory characteristics in chicken soup, the content of amino acids, organic acids, 5′-nucleotides, and mineral elements were determined in chicken soup sample. With the ginger added, free amino acids in chicken soup obviously increased and exceeded the total amounts in ginger soup and chicken soup. The content of glutamic acid (122.74 μg/mL) was the highest among 17 free amino acids in ginger chicken soup. Meanwhile, six organic acids detected in chicken soup all obviously increased, among which lactic acid (1523.58 μg/mL) and critic acid (4692.41 μg/mL) exceeded 1000 μg/mL. The content of 5′-nucleotides had no obvious difference between ginger chicken soup and chicken soup. Compared with chicken soup, ginger chicken soup had a smaller particle size (136.43 nm) and color difference (79.69), but a higher viscosity. With ginger added in chicken soup, the content of seven mineral elements was reduced, and the content of total sugar increased. Results from an electronic tongue indicated a difference in taste profiles among the soups. The taste components and sensory quality of chicken soup were obviously affected by adding the ginger.